Body size and risk of non‐Hodgkin lymphoma by subtype: A pooled analysis from six prospective cohorts in the United States. (29th March 2022) - Teras, Lauren R.; Bertrand, Kimberly A.; Deubler, Emily L.; Chao, Chun R.; Lacey, James V.; Patel, Alpa V.; Rosner, Bernard A.; Shu, Yu‐Hsiang; Wang, Ke; Zhong, Charlie; Wang, Sophia S.; Birmann, Brenda M.
Abstract: In 2022, more than 100 000 non‐Hodgkin lymphoma (NHL) diagnoses are expected, yet few risk factors are confirmed. In this study, data from six US‐based cohorts (568 717 individuals) were used to examine body size and risk of NHL. Over more than 20 years of follow‐up, 11 263 NHLs were identified. Hazard ratios (HRs) and 95% confidence intervals (CI) estimated associations with NHLs for adult body mass index (BMI), height, weight change, waist circumference and predicted fat mass. Adult height was broadly associated with NHL, but most strongly with B‐cell NHLs among non‐White participants (e.g. HRBLACK = 2.06, 95% CI: 1.62–2.62). However, the strongest association among the anthropometric traits examined was for young adult BMI and risk of diffuse large B‐cell lymphoma (DLBCL), particularly those who maintained a higher BMI into later adulthood. Individuals with BMI over 30 kg/m 2 throughout adulthood had more than double the DLBCL risk (HR = 2.67, 95% CI: 1.71–4.17) compared to BMI 18.5–22.9 kg/m 2 . Other anthropometric traits were not associated with NHL after controlling for BMI. These results suggest that sustained high BMI is a major driver of DLBCL risk. If confirmed, we estimate that up to 23.5% of all DLBCLs (and 11.1% of all NHLs) may be prevented with avoidance of young adult obesity.